2021
DOI: 10.1037/xge0000942
|View full text |Cite
|
Sign up to set email alerts
|

Explanations for norm violations affect preschoolers’ judgments of norm violators.

Abstract: Preschoolers commonly interpret how a group is as evidence for how individual group members should be—often leading to emphatic disapproval of norm violations (i.e., descriptive-to-prescriptive reasoning). The present research suggests that this tendency is shaped by how preschoolers explain group norm violations. In Study 1, preschoolers held norm violators accountable for their actions (e.g., they evaluated them as bad and withheld resources from them), suggesting that they construed norm violations as inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…One thought-provoking finding in Study 2 is that although children showed the effect of structural framing in their reasoning and evaluations (similar to e.g. Hussak & Cimpian, 2015;Van Wye et al, 2020, in which children were explicitly provided with different types of explanations), they still did not choose non-conforming peers over conforming ones as playmates. This finding suggests that merely inducing structural thinking might not be enough to mitigate children's behavioral sanctioning (or discrimination) of non-conforming peers, possibly because behavioral consequences are particularly hard to mitigate (see also Yang & Dunham, 2019).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…One thought-provoking finding in Study 2 is that although children showed the effect of structural framing in their reasoning and evaluations (similar to e.g. Hussak & Cimpian, 2015;Van Wye et al, 2020, in which children were explicitly provided with different types of explanations), they still did not choose non-conforming peers over conforming ones as playmates. This finding suggests that merely inducing structural thinking might not be enough to mitigate children's behavioral sanctioning (or discrimination) of non-conforming peers, possibly because behavioral consequences are particularly hard to mitigate (see also Yang & Dunham, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…Besides evaluations, Study 2 also investigates children's behavioral intentions (whether they choose to affiliate with non-conforming peers); these two critical attitudinal and behavioral choice measures probe the potential consequences of structural vs. non-structural reasoning. Unlike most past work on this topic that either did not probe the consequences of structural reasoning (Vasilyeva et al, 2018) or only probed evaluative judgments (Dunlea & Heiphetz, in press;Peretz-Lange et al, 2021;Van Wye et al, 2020), our work examined both evaluative judgments and behavioral intentions, providing a test of the effects of structural cues on a wider range of outcomes. As stated above, our goal is to test whether structural reasoning is impactful on attitudes and behavioral intentions even when preexisting beliefs are strong, as in many cases outside of laboratory settings where researchers and practitioners seek to reduce the negative consequences of stereotyping.…”
Section: The Present Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Broadly, internal information focuses on causes residing within an individual. Information about internal causes can either focus on temporary properties—including mental and emotional states, desires, preferences, and whims—or stable properties such as genetics, traits, and “essences.” Although internal properties can be temporary or stable, relatively more studies have focused on the consequences of attributing human characteristics to stable (e.g., Heiphetz, 2019; Hussak & Cimpian, 2018; Mandalaywala et al, 2018, 2019; Pauker et al, 2010, 2016; Rhodes et al, 2018), versus temporary (e.g., Van Wye et al, 2020), internal causes. To build on prior work in this area, we also focused on the ramifications of providing people with information about stable internal causes for social phenomena.…”
Section: Information About the Causes Of Human Characteristicsmentioning
confidence: 99%